SUPERVISI AKADEMIK DALAM BIDANG MULTIMEDIA PEMBELAJARAN GURU DI SMK YPC TASIKMALAYA - Atep Rurus Ruskala (Jurnal Abdi Ilmu, 2020)
This study uses a descriptive research method that seeks to describe and interpret objects in accordance with the real situation as it is. The research method was chosen with the aim of systematically describing the facts and characteristics, the subject or object being studied realistically. The research the researcher uses is a qualitative perspective, designed to contribute to practical theory, policy, social problems and action. Collecting data using observation techniques, interviews, documentation studies while for data processing techniques with qualitative reliability test, validity and data triangulation techniques. From the research results obtained by researchers in the field, the authors conclude that, (1) Academic supervision at YPC Tasikmalaya Vocational School still needs to be improved by giving priority to the process of forming and developing teacher professional abilities, the planning program used in the management of academic supervision at YPC Tasikmalaya Vocational School. carried out by coordinating through meetings with all teachers to determine the basis or basis for planning supervision, compiling a schedule for academic supervision plans, understanding the objectives of the supervision being carried out (2) The use of multimedia at SMK YPC Tasikmalaya still needs to be improved, especially focusing on management systems academics by providing a website in the form of a reel time academic management system (SMART), an electronic library, new student admissions, e-learning (electronic learning), online attendance and other facilities that are still in the process of being improved (3) Understanding level n teachers in the use of multimedia learning need to be improved with different educational backgrounds. Not all teachers have adequate multimedia information technology skills, even though teachers try to improve their ability to be able to visualize learning concepts to students, so that the multimedia learning process can be carried out. However, due to limitations there are academic supervision activities in the multimedia field of teacher learning at SMK YPC Tasikmalaya that have not been fully implemented. Furthermore, in overcoming these problems, it is necessary to improve learning facilities, increase human resources in the multimedia field systematically and comprehensively.